Strategi Pemasaran Produk Di Era Digital Pada UMKM - Syukron; Amron Zarkasih; Siti Lam'ah Nasution; Muhammad Raja Siregar; Rika Syahmewah Munthe (Asosiasi Dosen Akuntansi Indonesia, 2022)
Marketing strategy is very important in business processes. This process is the final process of a production. Today digital-based marketing is one of the breakthroughs in the marketing world and we are required to adapt to it. Service activities for MSMEs are carried out at the Rantau Prapat MSME service in collaboration with the Rantau Prapat Pratama Tax Service Office. This activity focuses on MSME participants in Labuhanbatu, namely briefing on how to market product strategies in the current digital era with a total of 30 MSME participants. The implementation method used was lectures and questions and answers to MSME entrepreneurs who were present at the forum. The results achieved are that MSMEs can independently market products with their respective strategies in the current digital era in accordance with sales targets, MSMEs know market share and market developments in the current digital era, and can use media such as marketplaces as a place for their online sales.